2023
DOI: 10.1177/10732748231159706
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CD47-SIRPα Signal Axis as Promising Immunotherapy in Ovarian Cancer

Abstract: Among the three primary gynecological malignancies, ovarian cancer has the lowest incidence but the worst prognosis. Because of the poor prognosis of ovarian cancer patients treated with existing treatments, immunotherapy is emerging as a potentially ideal alternative to surgery, chemotherapy, and targeted therapy. Among immunotherapies, immune checkpoint inhibitors have been the most thoroughly studied, and many drugs have been successfully used in the clinic. CD47, a novel immune checkpoint, provides insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 137 publications
(194 reference statements)
0
9
0
Order By: Relevance
“…CD47 had become a star anti-tumor molecule since its immune checkpoint (IC) identity was revealed [ 12 ]. Initially, CD47 was known as integrin-associated protein involved in inflammatory cell chemotaxis, adhesion, migration, and activation of anti-inflammatory response and platelets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CD47 had become a star anti-tumor molecule since its immune checkpoint (IC) identity was revealed [ 12 ]. Initially, CD47 was known as integrin-associated protein involved in inflammatory cell chemotaxis, adhesion, migration, and activation of anti-inflammatory response and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immunity may play a key role in this prognostic-protective effect, including activation and increased levels of cytotoxic T cells and TICs [ 36 , 37 ]. Previous studies have demonstrated that simultaneously high CD47 and positive PD-L1 expression on tumor cells could synergistically promote tumor development, and that dual-blockade could achieve better anti-tumor effects than single blockade of CD47 or PD-L1 [ 12 , 38 ]. Our study might reveal a novel and more common synergistic pro-tumor immunophenotyping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that CD47 may serve as an important biomarker for predicting response to immunotherapy [49,69]. Preclinical studies have demonstrated that blocking CD47 can enhance the efficacy of immunotherapy by enhancing immune cell Allows cells to evade immune surveillance [50,60,64] PI3K/Akt CD47 interacts with PI3K/Akt pathway Regulates cellular processes such as cell survival, proliferation, and migration [61,65] infiltration and inducing tumor cell death [70]. For instance, combination therapies incorporating CD47 blockade and checkpoint inhibitors have exhibited improved anti-tumor immunity and enhanced tumor regression [71].…”
Section: Evidence Of the Impact Of Cd47 Expression On Immunotherapy O...mentioning
confidence: 99%